Servqual Method Analysis of the Influence of Service Quality of Land and Building Rights Acquisition Fees (BPHTB) on Taxpayer Satisfaction - Atalya Kurnia Sari (Jurnal Ipteks Terapan, 2023)
The tax on the acquisition of land and building rights (BPHTB) is one of the regional revenue sources for Asahan Regency, which is collected from the public. During the implementation of the BPHTB, it provides results that annually obtain income up and down in achieving the specified target. This is related to public awareness as taxpayers in paying taxes. The higher the level of public awareness in paying taxes will affect the increase in tax revenue. the factor that influences public awareness in paying taxes is the level of trust in the effectiveness of the service system managed by the state or agency. The Asahan Regency Regional Revenue Management Office seeks to meet some of the growing needs of the community by increasing the services provided by taxpayers. With the expectation and reality evaluation questionnaire, it can be analyzed using the Service Quality method so that it can determine the level of service satisfaction. The results of the analysis of the system can assist agencies in determining criteria as benchmarks in their services, and it can be seen that the criteria are maintained and improved so that they can further improve the quality of their services.Keywords: Land and Building Rights Acquisition Tax, Service Quality, PHP, MySql.